A Survey of Health Behaviors of Students at University of Phayao according to Eight Principles of Syndrome Differentiation in Traditional Chinese Medicine (Ba Gang Bian Zheng) - Siriteerathitikul, Poonyaphat (Journal of Health Sciences and Wellness, 2021)
This study was survey research with the objectives to 1) study the health behaviors of students at the University of Phayao; 2) analyze and differentiate the early syndrome of students at the University of Phayao according to the Eight Principles of Syndrome Differentiation in Traditional Chinese Medicine (Ba Gang Bian Zheng), and 3) study the relationships between health behaviors and early syndrome of students at University of Phayao according to Ba Gang Bian Zheng principles. In this study, a questionnaire as a research instrument in collecting data from a total of 392 students at the University of Phayao. The analysis and differentiation of the syndrome showed that 18.62% of the syndrome could be classified as Exterior syndrome, 11.48% were Deficiency Cold syndrome and 10.20% were Excess Cold syndrome. For personal behaviors of students, it was found that the most common behaviors were staying up late, not getting enough, and not being active (with an average of 2.85 and 3.09, respectively). The behaviors with moderate frequency included consuming cold drinks or food, consuming hot drinks or food, consuming fast food, being hot-tempered, and being easily irritable (with an average of 5.68, 8.58, 6.24, and 5.41, respectively). The behaviors with low frequency included drinking alcohol and depression (with an average of 2.00 and 1.91, respectively). The analysis of relationships between behaviors and syndromes using Pearson’s chi-square test showed that staying up late and not getting enough sleep affected all the syndromes according to Ba Gang Bian Zheng principles (Exterior/Interior/Cold (Yin)/Hot (Yang)/ Deficiency / Excess syndrome), while emotion and not being active affected the Exterior/Interior/Hot (Yang)/ Deficiency/Excess syndrome, and drinking cold drinks and food affected the Cold syndrome. In addition, drinking hot drinks or food affected the Hot syndrome, and consuming fast food and drinking alcohol affected the Interior/Deficiency/Excess syndrome at the statistical significance level of p < 0.05 and p < 0.01.